# 3/2 plus 1/6 as a fraction 3/2 + 1/6 as a fraction provides the detailed information about what is 3/2 plus 1/6 in fraction and decimal form, and the answer with steps to understand how it is being calculated by using different methods.

3/2+1/6 equals to
3/2 + 1/6 = (?)
3/2 + 1/6 = [(3 x 6) + (1 x 2)]/(2 x 6)
= (18 + 2)/12
= 20/12
= (4 x 5)/(4 x 3)
= 5/3
3/2 + 1/6 = 5/3
3/2 plus 1/6 is equal to 5/3

where
3/2 is a fraction as an addend,
1/6 is a fraction as an addend,
5/3 is the sum of 3/2 and 1/6.

3/2 plus 1/6 as a decimal
3/2 + 1/6 = 5/3
5/3 = 1.6667
3/2+1/6 as a decimal is 1.6667
where
1.6667 is the sum of 3/2 and 1/6.

For values other than 3/2 plus 1/6, use this below tool:

## How-to: 3/2 + 1/6 = ?

The below workout with step by step calculation shows how to find what is 3/2 plus 1/6 in simplest form by using the following methods:
1. LCM method,
2. Cross multiplication method.

Problem and Workout - LCM Method:
What is 3/2 plus 1/6 as a fraction?

step 1 Observe the input parameters and what to be found:
Input:
Fraction A: 3/2
Fraction B: 1/6

What to be found?
3/2+1/6 = ?
Find what's the sum of 3/2 and 1/6.

step 2 Compare the denominators of fractions 3/2 and 1/6 to identify whether it is a like or unlike fraction addition. Since the denominators of given fractions 3/2 and 1/6 are not equal, it is said to be unlike fractions addition.

step 3For unlike fractions addition, find the LCM (least common multiple) of both denominators of fractions 3/2 and 1/6:
The LCM of 2 and 6 is 6.

step 4 Write the fractions 3/2 and 1/6 in the addition expression form and multiply LCM with all the numerators and denominators of both fractions.
=3/2+1/6
=(3 x 6)/(2 x 6)+(1 x 6)/(6 x 6)

step 5 Simplify the expression to have common denominator:
=9/6+1/6

step 6 Take the common values out and rewrite the above expression like the below:
=1/6 x (9/1+1/1)
=1/6 x (9 + 1)

step 7Simplify the above expression further:
=1/6 x 10
= 10/6
=5/3
3/2+1/6=5/3

Hence,
3/2 plus 1/6 equals to 5/3 in fraction.

Problem and Workout - Cross Multiplication Method
step 1 Observe the input parameters and what to be found:
Input:
Fraction A: 3/2
Fraction B: 1/6

What to be found?
3/2+1/6 = ?
Find what's the sum of 3/2 and 1/6.

step 2 Find the product of numerator of Fraction A and denominator of Fraction B (3 x 6), find the product of numerator of Fraction B and denominator of Fraction A (1 x 2), and find the product of both denominators of Fraction A and Fraction B (2 x 6) and rewrite the equation as like the below:
= (3 x 6) + (1 x 2)/(2 x 6)

step 3 Simplify and rewrite the fraction:
= (18 + 2)/12
= 20/12
= 5/3
3/2+1/6 = 5/3
Hence,
3/2 plus 1/6 = 5/3 